2014
DOI: 10.1186/1475-925x-13-153
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine supported by Augmented Reality: an interactive guide for untrained people in performing an ECG test

Abstract: BackgroundIn many telemedicine applications, the correct use of medical device at the point of need is essential to provide an appropriate service. Some applications may require untrained people to interact with medical devices and patients: care delivery in transportation, military actions, home care and telemedicine training.Appropriate operation of medical device and correct connection with patient’s body are crucial. In these scenarios, tailored applications of Augmented Reality can offer a valid support b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“…53 Nearly one-third of all studies (n=8) either had no evaluation tool or did not report any validity of the instrument used. [28][29][30][31][32][33][34][35] The qualitative study involved semi-structured face-toface interviews that explored the needs and challenges of applying AR for healthcare education. The study demonstrated a detailed clarity and rigor according to the individual AQRAME score of all three authors corresponding to 12 (JG), 11.5 (CBS), and 12 (PD).…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…53 Nearly one-third of all studies (n=8) either had no evaluation tool or did not report any validity of the instrument used. [28][29][30][31][32][33][34][35] The qualitative study involved semi-structured face-toface interviews that explored the needs and challenges of applying AR for healthcare education. The study demonstrated a detailed clarity and rigor according to the individual AQRAME score of all three authors corresponding to 12 (JG), 11.5 (CBS), and 12 (PD).…”
Section: Methodological Qualitymentioning
confidence: 99%
“…41,47,48 Eight studies implemented headmounted display. 27,28,38,40,[43][44][45][46] Two studies utilized the same head-mounted display. 40,43 The head-mounted display-integrated applications had marker-based recognition in four of the studies.…”
Section: Technical Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…En la investigación las aportaciones han surgido desde diferentes áreas, esto conecta con la idea sobre la RA indicada en muchos ámbitos, y compartimos con Kaufmann, Schmalstieg y Wagner (2000) que esta técnica viene a apoyar la explicación de contenidos complejos propios de las matemáticas y geometría, por ejemplo a través de mediciones virtuales (Figura 2). No obstante destacamos la novedad y el enriquecimiento instrumental en las tareas en general, que implica el trabajo sobre contenidos reales con la información virtual superpuesta, y que ya tiene uso directo en campos vitales para el desarrollo como la telemedicina (Bifulco, et al, 2014). Esta técnica también parece ser útil cuando se requiere una interacción con usuarios que desconocen un determinado aspecto, así Zhu et al (2014) destacan cómo las aplicaciones RA pueden ofrecer un apoyo valioso incluso con personas no preparadas previamente, observando y respetando los protocolos de funcionamiento.…”
Section: Discusión Y Propuestasunclassified